Hypertension in Jordan: Prevalence, Awareness, Control, and Its Associated Factors - Yousef Khader; Anwar Batieha; Hashem Jaddou; Sukaina I. Rawashdeh; Mohammed El-Khateeb; Dana Hyassat; Albaraa Khader; Kamel Ajlouni (International Journal of Hypertension)
Objectives. Determine the prevalence, awareness, and control rates of hypertension and their associated factors among Jordanian adults. Methods. A multistage sampling technique was used to select a nationally representative sample of adults from the population of Jordan. Trained interviewers collected data using a comprehensive structured questionnaire, measured anthropometric parameters, and collected blood samples. Results. This study included a total of 1193 men and 2863 women aged ranged from 18 to 90 year with a mean (SD) of 43.8 (14.2) year. The age-standardized prevalence was 33.8% among men and 29.4% among women. Of those with hypertnsion, 57.7% of men and 62.5% of women were aware of hypertension. Only 30.7% of men and 35.1% of women who were on antihypertensive medications had their blood pressure controlled. From 2009 to 2017, there was nonsignificant decrease in hypertension prevalence of 2.7% among men and 1.1% among women. However, the rate of hypertension awareness increased significantly among men and among women. Discussion. Almost one-third of Jordanian adults had hypertension. Interventions that target modifiable risk factors of hypertension, might decrease blood pressure, and even prevent the development of hypertension should be implemnted.